1979
DOI: 10.1001/jama.1979.03290350017012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physicians' Attitudes Toward Telling the Cancer Patient

Abstract: In answer to a questionnaire administered in 1961, 90% of responding physicians indicated a preference for not telling a cancer patient his diagnosis. To assess attitudinal changes, the same questionnaire was submitted to 699 university-hospital medical staff. Of 264 respondents, 97% indicated a preference for telling a cancer patient his diagnosis--a complete reversal of attitude. As in 1961, clinical experience was the major policy determinant, but the 1977 population emphasized the influence of medical scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
221
2
9

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(233 citation statements)
references
References 7 publications
1
221
2
9
Order By: Relevance
“…We then fit the model a second time, constraining all comparable parameters to be equal across groups. 6 If we accept the first model (i.e., prefer it to the second), we conclude that the groups perform differently as surrogates. If we accept the second model, we conclude that the groups do not perform differently as surrogates.…”
Section: Model-the Structural Equations Describing the Model Arementioning
confidence: 92%
See 1 more Smart Citation
“…We then fit the model a second time, constraining all comparable parameters to be equal across groups. 6 If we accept the first model (i.e., prefer it to the second), we conclude that the groups perform differently as surrogates. If we accept the second model, we conclude that the groups do not perform differently as surrogates.…”
Section: Model-the Structural Equations Describing the Model Arementioning
confidence: 92%
“…Subsequent psychosocial research showed that the awareness that one is dying does not emotionally harm a patient (Kübler-Ross 1969). Physician attitudes evolved such that the standard for care is now full disclosure and collaboration among patients, health care providers, and surrogate decision-makers in cases where the patient is unable to convey his or her own treatment preferences (Brody 1997;Novack et al 1979;Snyder and Leffler 2005). Changes in physician attitudes have occurred alongside policy changes: In 1990, Congress passed the Patient Self-Determination Act (PSDA) to ensure that dying people have a greater say in their care.…”
Section: Introductionmentioning
confidence: 99%
“…This result was higher than those found in other studies where questionnaires were addressed to physicians (Novack et al, 1979;Smith & Swisher, 1998;Loge et al, 1996), and certainly higher than in some of those carried out in Southern European countries, including Portugal (Santos et al, Cancer diagnosis disclosure from Portuguese physicians 3 1994; Gonçalves & Castro, 2001). It reveals a substantial shift in the opinions and attitudes of physicians with regard to telling the truth to cancer patients.…”
Section: Discussionmentioning
confidence: 56%
“…On rare occasions, a doctor may ask a patient to go to ED as a terminally ill patient reflects their defeat to maintain health and by having no magic bullet to fix things, causes avoidance of the patient. Knowing the duration of suffering brings desire to do more in the physicians like in child birth, traumatic injury or post-operative pain [15].…”
Section: Ethics Of Ulysses' Contractmentioning
confidence: 99%